Women's experiences in the transition to menopause: a qualitative research - Mansoureh Refaei; Soraya Mardanpour; Seyedeh Zahra Masoumi; Parisa Parsa (BMC, 2022)
Abstract Background Around the time of transition to menopausal period, women experience mental, and psychological disorders that require adequate attention to these symptoms. This study aimed to explore the experiences of women in the face of premenopausal symptoms. Methods This qualitative study was conducted using a content analysis method in Javanrood, Iran, in 2020. The data were collected through in-depth semi-structured face to face interviews with 16 premenopausal using interview guide in a private room in comprehensive health centers. The women inclusion criteria were approaching menopause, having irregular menstruation, and having no disease or medication that affects menstruation. Furthermore, the exclusion criteria were the absence of menstruation for more than 12 months, and the women's refusal to continue the interview. The participants were selected using purposive sampling and sampling continued until data saturation. The collected data were analyzed with MAXQDA10 software following the multi-step method proposed by Graneheim and Lundman. Results The participants' mean age was 47 ± 2.98 years. The data analysis revealed 5 categories including: "menopause and aging", "life transformation", confrontation of fear and hope", "life adjustment", and "need to facilitate the transition time". Conclusion This study suggested the women's experience of the transition to menopause was characterized by the fear of the future and its consequences and the need for reassurance about it. Besides, the women sought solutions to their problems in health care providers, peers, and the family.